Cognitive and Behavioral Adaptation Strategies in Learning Financial Derivatives: A Qualitative Study on Undergraduate Students - Rachman, Izmirta (PT Mattawang Mediatama Solution, 2025)
Financial derivatives constitute a challenging course for undergraduate students due to the complexity of the underlying concepts and calculations. This study explores students’ cognitive and behavioral adaptation strategies in learning financial derivatives, employing financial literacy theory, cognitive and behavioral learning theories, and risk management theory as analytical frameworks. A qualitative approach was adopted, involving in-depth interviews with 21 seventh-semester students from a private university in Jakarta, selected through purposive sampling. The data were analyzed thematically and supplemented with quantitative counts of adaptation strategy frequency. The findings indicate that students struggle to comprehend technical terminology and apply derivative concepts, challenges that are further exacerbated by a lack of contextual learning. The most common adaptation strategies include case-based learning, self-directed study, group discussions, and the use of technology such as artificial intelligence and social media. The study highlights the need for more interactive, simulation-based teaching methods and expanded access to digital learning resources.